2013
DOI: 10.1021/nn401011n
|View full text |Cite
|
Sign up to set email alerts
|

Nanolayered siRNA Dressing for Sustained Localized Knockdown

Abstract: The success of RNA interference (RNAi) in medicine relies on the development of technology capable of successfully delivering it to tissues of interest. Significant research has focused on the difficult task of systemic delivery of RNAi; however its local delivery could be a more easily realized approach. Localized delivery is of particular interest for many medical applications, including the treatment of localized diseases, the modulation of cellular response to implants or tissue engineering constructs, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 50 publications
0
41
0
Order By: Relevance
“…Layer-by-Layer (LbL) technology has been demonstrated in a myriad of biomedical applications for delivery from a broad range of material surfaces, including stainless steel and degradable polymer matrices. [19] We have previously demonstrated that LbL incorporation and delivery of siRNA can achieve significant and sustained knockdown of reporter genes in vitro [20] , although the ability to translate these results to a more complex environment in vivo remained unknown. Therefore, developing this technology to effectively deliver siRNA to a localized area in vivo using a meaningful therapeutic gene target presents a significant advancement for the treatment of site-specific disorders, including DFUs as well as cardiovascular diseases, cancers, and transplant rejection.…”
Section: Introductionmentioning
confidence: 99%
“…Layer-by-Layer (LbL) technology has been demonstrated in a myriad of biomedical applications for delivery from a broad range of material surfaces, including stainless steel and degradable polymer matrices. [19] We have previously demonstrated that LbL incorporation and delivery of siRNA can achieve significant and sustained knockdown of reporter genes in vitro [20] , although the ability to translate these results to a more complex environment in vivo remained unknown. Therefore, developing this technology to effectively deliver siRNA to a localized area in vivo using a meaningful therapeutic gene target presents a significant advancement for the treatment of site-specific disorders, including DFUs as well as cardiovascular diseases, cancers, and transplant rejection.…”
Section: Introductionmentioning
confidence: 99%
“…2a) [72]. When 25 layers of the [Chi/siRNA] film were assembled onto a [Poly2/DS] 20 coated suture, a total of 2.1 ± 0.3 μg/cm of siRNA was incorporated.…”
Section: Resultsmentioning
confidence: 99%
“…In our experiment, the release profile of the LbL film was gradual and linear within the duration of 1 week, which is consistent with the findings of another report. 31 The electrostatically anchored multilayer structure provided a controlled release of the loading cargo, which is pivotal for local drug delivery in order to obtain a sustained effect. [32][33][34] H1299 originates from epithelial lung cancer and has a prominent ability of endocytosis.…”
Section: Discussionmentioning
confidence: 99%